Impact of the menstrual cycle and barriers to football and futsal performance in Portuguese players: a survey-based cross-sectional study - Santos, Cristiana; Lopes, Mário; Brito, João; Kryger, Katrine Okholm; Wilke, Carolina; Travassos, Bruno (Frontiers in Psychology, 2025)
IntroductionThe objective of this study was to investigate the perceived impact of the different phases of the menstrual cycle on football and futsal participation and identify barriers that may limit the performance and participation of Portuguese female players across competition levels.MethodsAn online survey was conducted with the following inclusion criteria: registered participation in official football or futsal Portuguese leagues, an age of 18 years or older, and perceived regular menstrual cycles. A total of 197 answers were obtained and analyzed.ResultsThe majority of participants were 18-25 years old (61%), and 59% played futsal. Top-tier league players represented 15% of respondents, mid-tier 26%, and low-tier 59%. For the majority of respondents, the first 3 days of menstruation were perceived as having the most negative impact (66%), with abdominal pain, bloating, and breast tenderness being the most common symptoms. Players also associated the menstrual phase with decreased performance (endurance and power) and self-confidence, whereas they generally felt more confident and motivated during ovulation. No significant differences were found between sports (football and futsal) or competition levels in the perceived impact on performance and participation (p > 0.05). Overall, 53% of the players reported a perceived lack of knowledge and trust in their coach and other staff members to talk openly about menstrual health. The most cited external barrier to sports participation was the fear of leaking. To address the identified challenges, five intervention levels were proposed: communication, comprehension, education, equipment, and facilities.DiscussionThese findings emphasize the need for better communication, education, and structural support to reduce menstruation-related barriers.